MANAJEMEN SERTIFIKASI JALUR PORTOFOLIO BAGI GURU SEKOLAH DASAR DI KOTA SEMARANG - Indarti, Indarti (Jurnal Penelitian dan Evaluasi Pendidikan, 2011)
Penelitian ini bertujuan untuk mengetahui perencanaan, pengorganisasian, pelaksanaan, dan pengawasan sertifikasi jalur portofolio bagi guru Sekolah Dasar di Kota Semarang. Peneliti-an ini menggunakan pendekatan kualitatif, dilaksanakan di Di-nas Pendidikan Kota Semarang. Subjek penelitian terdiri dari Kepala Bidang Pendidik dan Tenaga Kependidikan Dinas Pen-didikan, kepala sekolah, dan guru. Teknik pengumpulan data menggunakan metode wawancara, observasi proses pembelajar-an, penelusuran dokumen perencanaan pembelajaran dan por-tofolio. Data yang diperoleh dianalisis dengan analisis kualititatif melalui langkah pengumpulan, penyajian, reduksi, dan penarik-an kesimpulan. Hasil penelitian menunjukkan bahwa: (1) Peren-canaan sertifikasi jalur portofolio tidak berjalan dengan baik, dari aspek sosialisasi prosedur tidak tuntas dan data tidak valid, (2) Pengorganisasian sertifikasi jalur portofolio tidak berjalan dengan baik, dari aspek penyusunan dan verifikasi dokumen portofolio tidak sesuai dengan buku panduan, (3) Pelaksanaan sertifikasi guru jalur portofolio tidak berjalan dengan baik, (4) Pengawasan sertifikasi jalur portofolio tidak berjalan dengan baik. Kata Kunci: manajemen, sertifikasi guru, profesi  ______________________________________________________________THE MANAGEMENT OF THE CERTIFICATION THROUGH THE PORTFOLIO SYSTEM FOR ELEMENTARY SCHOOL TEACHERS IN SEMARANG CITY Abstract This study aims to investigate the planning, organizing, actuating and controlling functions in the certification through the portfolio system for elementary school teachers in Sema-rang City. This study employed the qualitative approach, con-ducted in the Office of Education of Semarang City. The research subjects consisted of the Head of the Educator and Educational Personnel Section in the Office of Education, principals, and teachers. The data collecting techniques included interviews, observations, and document tracing. The data were collected through interviews, supported by observations on learning processes and tracing documents of lesson plans and portfolio. The collected data were analyzed using the qualitative technique involving steps of collection, display, reduction, and conclusion drawing. The results of the study are as follows: (1) the planning of the portfolio system certification does not run well; from the aspect of socialization, procedures are income-plete and the data are invalid, (2) organization of portfolio system certification does not run well; from the aspects of portfolio preparation and verification, the documents are not in accordance with the guide books, (3) the actuation of the portfolio system certification does not run well, (4) the control of the portfolio system certification does not run well.Keywords: management, teacher certification, profession